Substitution of Tempeh and Adition of Dates in The Manufacture of Snack Bar as High Protein and Iron Snack - Tiara Dela Satifa; Asrul Bahar (International Journal on Food, Agriculture and Natural Resources, 2023)
Snack bar is a ready-to-serve and nutrient-dense snack, making this product popular among people with a modern and practical lifestyle. The raw material for making snack bars in general is soy flour added with dried fruit. Along with the development of science and technology, efforts can be made to improve the quality and nutritional content of snack bar products. Tempe is a processed soybean product that has a higher nutritional content and quality than pure soybeans. Dates are one of the fruits that are abundantly available and have a complete nutritional composition. As an effort to improve the quality and nutritional content, research was conducted on the substitution of tempeh and the addition of dates in the manufacture of soy flour-based snack bars. Quantitative research using the experimental method using a completely randomized design (CRD), 3x2 factorial design resulted in 6 treatment formulas. Formula 4 with 30% tempeh substitution and 40% addition of dates became the best product based on the results of statistical analysis of product organoleptic assessment using a two-way ANOVA and DMRT follow-up test involving 50 panelists. The nutritional content test was carried out on formula 4 with the result that every 100 grams of product contained 19% protein and 4.62 mg of iron. The best snack bar formula per serving size of 15 g has a higher protein content than the three comparison products. Existing snack bars using soy flour as raw material are known to have a lower protein content compared to snack bars made from soybean flour substituted with tempeh. Likewise, the protein content in tempeh- based snack bars in the previous study and the USDA peanut-based snack bars still had lower protein content. In this regard, the combination of soy flour and tempeh in the manufacture of snack bars can increase the protein content of the product. In addition, the iron content of snack bars in this study was higher than USDA product 1980811. This is related to the composition of one of the raw materials for its manufacture, namely dates, which are known to be rich in iron minerals.